391OSetting up breast services improvements and learning bridges in Kyrgyzstan: The SILK project. (24th November 2019) - Pagani, O; Del Grande, M; Peccatori, F; de Wolf, C; Pruneri, G; Mattei, L; Richetti, A; Presilla, S; Sabyrbekova, T; Bakirova, N; Soldak, T; Abdyldaev, D; et al.
Abstract: Background: In Kyrgyzstan, a low-middle income Central-Asia republic, breast cancer (BC) management does not meet minimal standards: ∼70% of women are diagnosed late and do not receive adequate treatments. Setting up BC services is a health priority. Methods: In 2011, the Swiss Development Cooperation in Central Asia audited for a BC project in Kyrgyzstan. The audit found a dramatic situation in imaging, histologic diagnosis and treatment (local and systemic). A multi-step program was funded, supported by the European School of Oncology (ESO), the Swiss Cancer League and the Swiss Association against Cancer in close collaboration with the local ONG Ergene (Europa Donna member), the Swiss Embassy and the Kyrgyz Ministry of Health. The first priorities were mammographic and histologic diagnosis. From 2017, Swiss and Italian breast specialists periodically visited Kyrgyzstan to supply materials, teach health professionals and trace progress and problems; Kyrgyz doctors were trained in Switzerland and Italy, patients were provided educational support and devices (prostheses, wigs). Results: Improvements were significant and fast. The mammography quality is now acceptable and the pathologists routinely assess hormonal receptors, HER-2 and Ki-67 expression and biomarkers for differentiating tumor subtypes. Diagnostic and therapeutic guidelines have been implemented with local physicians. Thanks to a Canadian government donation, two Linear Accelerators and one Computed Tomography for radiotherapy planning are being purchased, replacing old, unsafe equipment. A US ONG assisted in chemotherapy regimen implementation. Current steps involve training of radiation oncologists, medical physicists, technicians and surgeons in modern BC loco-regional approaches, discussing the availability of drugs of the WHO list of essential medicines, establishing tele pathology and mobile mammography. Conclusions: The SILK project shows effective BC cooperative programs in low-middle income countries are feasible. Strict and continuous collaboration with local governments, organizations and health professionals is vital to ensure their success. SILK is a model adaptable and exportable to other critical situations across the world. Legal entity responsible for the study: European School of Oncology. Funding: European School of Oncology, Swiss Cancer League. Disclosure: G. Pruneri: Honoraria (self): Roche Foundation Medicine. All other authors have declared no conflicts of interest.